2021
DOI: 10.1111/mmi.14781
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of the KaiC‐like protein ArlH inhibits oligomerization and interaction with ArlI, the motor ATPase of the archaellum

Abstract: Motile archaea are propelled by the archaellum, whose motor complex consists of the membrane protein ArlJ, the ATPase ArlI, and the ATP‐binding protein ArlH. Despite its essential function and the existence of structural and biochemical data on ArlH, the role of ArlH in archaellum assembly and function remains elusive. ArlH is a structural homolog of KaiC, the central component of the cyanobacterial circadian clock. Since autophosphorylation and dephosphorylation of KaiC are central properties for the function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 84 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…The ~36° steps, on the other hand, were hypothesised to be either associated with the hypothetical presence of 9–10 monomers of the modulator ArlH in the motor complex (as observed by Chaudhury et al, 2016 ), or motor slippage. Recent evidence suggests that ArlH forms a hexamer in the motor ( Sousa Machado et al, 2021 ), indicating the 9–10 stoichiometry of ArlH observed in previous single particle cryoEM data ( Chaudhury et al, 2016 ) may have been an artefact of sample preparation. A more recent calculation indicated that the torque output of H. salinarum archaella is 160 pN.nm regardless of its load ( Iwata et al, 2019 ).…”
Section: The Biophysics Of the Archaellum Motormentioning
confidence: 95%
See 4 more Smart Citations
“…The ~36° steps, on the other hand, were hypothesised to be either associated with the hypothetical presence of 9–10 monomers of the modulator ArlH in the motor complex (as observed by Chaudhury et al, 2016 ), or motor slippage. Recent evidence suggests that ArlH forms a hexamer in the motor ( Sousa Machado et al, 2021 ), indicating the 9–10 stoichiometry of ArlH observed in previous single particle cryoEM data ( Chaudhury et al, 2016 ) may have been an artefact of sample preparation. A more recent calculation indicated that the torque output of H. salinarum archaella is 160 pN.nm regardless of its load ( Iwata et al, 2019 ).…”
Section: The Biophysics Of the Archaellum Motormentioning
confidence: 95%
“…ArlI is the hexameric ATPase, which localises to the cytosolic side of the plasma membrane, probably owing to its interaction with the platform protein ArlJ, whose structure has not yet been determined ( Reindl et al, 2013 ). ArlH is an auto-kinase that interacts with ArlI, modulating its activity and perhaps controlling when the ATPase assembles or rotates the filament ( Chaudhury et al, 2016 ; Sousa Machado et al, 2021 ). The filament structure has been obtained from P. furiosus (5O4U; Daum et al, 2017 ), and the remaining structures from Sulfolobus acidocaldarius proteins 5TUG ( Tsai et al, 2020 ); 4IHQ ( Reindl et al, 2013 ); and 4YDS ( Chaudhury et al, 2016 ).…”
Section: The Archaellum Filamentmentioning
confidence: 99%
See 3 more Smart Citations